2001
DOI: 10.1093/clinchem/47.9.1688
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Metabolism and Bone Metabolism Markers in Healthy Adults during 16 Weeks of Bed Rest

Abstract: Background: The associations between nitrogen metabolism and bone turnover during bed rest are still not completely understood. Methods: We measured nitrogen balance (nitrogen intake minus urinary nitrogen excretion) and biochemical metabolic markers of calcium and bone turnover in six males before head-down tilt bed rest (baseline), during 2, 10, and 14 weeks of immobilization, and after reambulation. Results: The changes in nitrogen balance were highest between baseline and week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 28 publications
1
21
2
Order By: Relevance
“…Enhanced osteoclast activity is seen in astronauts or people in bed rest (3,4,17,19). In the ambulatory control phase, the volunteers showed a daily calcium excretion of 206 mg. During bed rest, calcium excretion rose significantly to 240 mg/day while their diet was unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced osteoclast activity is seen in astronauts or people in bed rest (3,4,17,19). In the ambulatory control phase, the volunteers showed a daily calcium excretion of 206 mg. During bed rest, calcium excretion rose significantly to 240 mg/day while their diet was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (7,18) have provided evidence for a close correlation between bone mass and muscle mass. Recent human studies (2,17) have also demonstrated that body nitrogen and muscle mass rapidly decrease with bed rest. Scheld et al (17) have even shown that there is a rapid loss of body nitrogen during the first 2 wk of bed rest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of normal volunteers placed on bed rest indicate that urinary CTx and NTx excretion increase significantly after 24 hours, no Early changes in formation markers predict later changes in density 49 In a 16-week study of bed rest in volunteers, markers of bone formation were reduced and markers of bone resorption increased, demonstrating the mechanisms for the profound and rapid loss of bone in immobilized patients. 50 In a long-term cross-sectional study of paraplegic men with spinal cord injuries, bone turnover patterns changed over time. 51 During the first year after injury, urinary deoxypyridinoline excretion was markedly elevated, whereas blood total alkaline phosphatase and osteocalcin levels were normal to slightly elevated.…”
Section: In Immobilization-induced Osteoporosismentioning
confidence: 99%
“…Scheld reported that serum osteocalcin was already reduced and renal calcium and phosphorus excretions were increased at the second week during bed rest. 22 Kim et al showed that levels of osteocalcin declined with an absolute increase in bone resorption and reduced bone formation after simulated microgravity for 14 days. 23 During 90-day bed rest, osteocalcin and bone resorption markers such as serum RANKL, OPG did not show consistent change at all time points.…”
Section: Discussionmentioning
confidence: 99%